The Application Jigsaw With Aid of Audiovisual Media to Improve Learning Outcomes of Class X3 Students of SMA Muhammadiyah 1 Surakarta - Mulyanto, Cicuk; Sudarno, Sudarno; Octoria, Dini (Economic Education and Entrepreneurship Journal, 2024)
This research was carried out with the aim of improving the learning outcomes of class X3 Muhammadiyah 1 Surakarta High School through the applications of Jigsaw method with the aid of audiovisual learning media in the economic subjects of class X3 of Muhammadiyah 1 High School Surakarta. This research uses the Classroom Action Research (CAR) carried out at the Muhammadiyah High School 1 Surakarta class X 3 with a total of 22 students. The study uses data collection techniques such as interviews, observations, test, and documentation using data triangulation analysis techniques. The learning outcomes of students before implementing Jigsaw assisted by audiovisual media were 18.18% of students who were able to achieve the specified KKTP with an average value of 67. Student learning outcomes increased significantly after the first cycle of action was carried out to 77.27% of students who had exceeded the predetermined KKTP with an average value of 85,6. The increase in learning outcomes continued to occur in the implementation of cycle II, amounting to 95.45% of students exceeding the KKTP with an average value of 90,2. Based on the results of the research conducted, it can be concluded that the application of the Jigsaw learning method with the help of audiovisual media can improve student learning outcomes.Keywords: Jigsaw, Audiovisual Media, Learning OutcomesDOI: http://dx.doi.org/10.23960/E3J/v7i1.78-82